Detection by in situ hybridization of specific high risk HPV in archival tissue of invasive cervical carcinoma and cervical intraepithelial neoplasia using specific biotynylated HPV DNA probe in conjunction with P53 and Rb gene protein expression - Othman, Nor Hayati (2002)
Cancer of the cervix is the second cause of cancer deaths among females in Malaysia after breast cancer. Penang, a state which has an up to date cancer registry records an annual incidence of 16 cases per 100,000 females. For the past twenty years or so Annual Reports of Ministry of Health recorded an average of 2200 new cases per year (Ministry of Health Annual Reports 1980-2000). This number is higher than the speculated 16 cases per 100,000 females in this country where the population of females is about 10.5 million. Cancer of the cervix is a preventive disease as the precursor cancer cells can be easily detected provided the women do regular screening tests called Pap Smear. The etiology is Human Papilloma Virus (HPV) in most cases and although there are ways to prevent transmission of the organisms, this is not often possible as the infection in the males are mainly asymptomatic.